Mate recognition and reproductive isolation in the sibling species Spodoptera littoralis and Spodoptera litura - Saveer, Ahmed M.; Becher, Paul G.; Birgersson, Göran; Hansson, Bill S.; Witzgall, Peter; Bengtsson, Marie (Frontiers in Ecology and Evolution, 2014)
Mate recognition is crucial for reproductive isolation and for maintaining species integrity. Chemosensory-mediated sexual communication with pheromones is an essential component of mate recognition in moths. Confronted with sex pheromone stimuli released from conspecific and closely related heterospecific females, which partially overlap in chemical composition, male moths are under strong selection to recognize compatible mates. Here, we investigated the role of pheromone signals in premating communication in the sibling species Spodoptera littoralis and S. litura (Lepidoptera, Noctuidae). Further, we measured the reproductive consequence of conspecific vs. heterospecific matings. Both species use Z9,E11-14:Ac as the major pheromone compound, and the 11-component blend found in pheromone glands of S. littoralis comprises the compounds found in S. litura. Accordingly, S. littoralis and S. litura males readily responded to conspecific and heterospecific calling females in no-choice behavioural tests. In contrast, in a dual-choice test, S. littoralis males choose conspecific calling females, whereas S. litura males did not discriminate between conspecific and heterospecific females. In S. littoralis females, heterospecific matings had a negative fitness effect as compared to conspecific matings. Female longevity, egg-laying and hatching of larvae were significantly reduced by matings with heterospecific males. Reciprocal crossings, between S. litura females and S. littoralis males, were prevented by genital morphology, which is consistent with reduced heterospecific attraction of S. littoralis males in a dual-choice assay. On the other hand, matings between S. littoralis females and S. litura males, under a no-choice situation, show that interspecific matings occur in zones of geographical overlap and corroborate the idea that mate quality, in these closely related species, is a continuous and not a categorical trait.